2003
DOI: 10.1289/ehp.5457
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-insulin-dependent diabetes mellitus and related vascular diseases in southwestern arseniasis-endemic and nonendemic areas in Taiwan.

Abstract: There is evidence indicating that ingestion of arsenic may predispose the development of diabetes mellitus in arsenic-endemic areas in Taiwan. However, the prevalence of diabetes and related vascular diseases in the entire southwestern arseniasis-endemic and nonendemic areas remains to be elucidated. We used the National Health Insurance Database for 1999-2000 to derive the prevalence of non-insulin-dependent diabetes and related vascular diseases by age and sex among residents in southwestern arseniasis-endem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
111
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 47 publications
(47 reference statements)
2
111
0
Order By: Relevance
“…3 Several studies have reported an association with arsenic exposure and diabetes mellitus. [3][4][5][6][7][8] Association of arsenic exposure with non-communicable diseases including Worldwide prevalence of diabetes mellitus is increasing in alarming way and is becoming a top cause of death. Every six seconds a person dies due to diabetes and it is projected that by 2030 diabetes will be the 7th leading cause of death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Several studies have reported an association with arsenic exposure and diabetes mellitus. [3][4][5][6][7][8] Association of arsenic exposure with non-communicable diseases including Worldwide prevalence of diabetes mellitus is increasing in alarming way and is becoming a top cause of death. Every six seconds a person dies due to diabetes and it is projected that by 2030 diabetes will be the 7th leading cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…14 In different studies, higher prevalence of diabetes mellitus was found amongst the arsenic exposed population compared to that of an arsenic non-exposed population. [4][5][6][7] A study conducted in Bangladesh also revealed such association amongst the arsenic exposed population having keratosis due to chronic arsenic toxicity. 9 Arsenicosis, the illness due to chronic arsenic toxicity is reported to occur more commonly amongst the young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular diseases, abnormal pigmentation, Raynand´s syndrome, acrocyanosis, hyperkeratosis, gangrene of fingers, ischemia of the tongue, diabetes, thrombosis, cerebral vascular disease, especially cerebral infarction, coronary artery occlusions, and other cardiovascular diseases (CVD) has been associated with As exposure [10][11][12][23][24][25][26][27][28] . Less common complications such as liver enlargement (hepatomegaly), splenn enlargement (splenomegaly) and fluid in the abdomen (ascitis) also has been cited 29 .…”
Section: Introductionmentioning
confidence: 99%
“…This is somewhat surprising because arsenic exposure has been linked to type 2 diabetes since 1950 when a case report documented a patient developing type 2 diabetes after receiving intravenous arsenical treatment for sexually transmitted diseases. 6 However, research efforts on the role of arsenic in diabetogenesis did not intensify until populationbased epidemiologic studies published in the 1990s from Taiwan [7][8][9] and Bangladesh 10 demonstrated that chronic exposure to high levels of arsenic from drinking water is associated with a higher prevalence of type 2 diabetes.…”
mentioning
confidence: 99%
“…Also, extrapolating from chronic high-dose effects to chronic low-dose effects of arsenic exposure on type 2 diabetes was debatable since many of the drinking water wells in Taiwan and Bangladesh contained several hundred micrograms of arsenic per liter. 7,9,10 In this month's issue of JAMA, Navas-Acien et al 11 are the first authors to report a positive association between low-level arsenic exposure and the prevalence of type 2 diabetes in the United States. Using newly available urinary arsenic data from National Health and Nutrition Examination Survey, a population-based survey conducted by the Centers for Disease Control and Prevention that collects information on the health and nutrition of the US population, the authors report a 3.6-fold increase in the odds of diabetes for participants with the highest total urinary arsenic concentrations as compared with participants with the lowest total urinary arsenic concentrations.…”
mentioning
confidence: 99%